2007
DOI: 10.1037/cjbs2007_2_110
|View full text |Cite
|
Sign up to set email alerts
|

A more accurate approach to measuring the prevalence of sexual harassment among high school students.

Abstract: The present study surveyed the prevalence of sexual harassment among high school students. A total of 1,582 students from 18 schools completed a version of the American Association of University Women (1993) survey. Reported sexual harassment events were restricted to those that: a) had been experienced first-hand, b) had occurred within the preceding two weeks, and c) were reported by students who were notably upset by their experiences. Despite this stringent approach, sexual harassment was found to be a sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
6

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 17 publications
1
13
0
6
Order By: Relevance
“…This is in agreement with the findings of Walsh et al (2007) and Mutekwe et al (2012) that the perpetrator or perpetrators were mostly male.…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…This is in agreement with the findings of Walsh et al (2007) and Mutekwe et al (2012) that the perpetrator or perpetrators were mostly male.…”
Section: Resultssupporting
confidence: 82%
“…Walsh et al (2007) found in their study on the prevalence of sexual harassment in high school that 9% of learners reported the gender of the perpetrator(s) to be male, 2% reported the gender of the perpetrator(s) to be female and 2% of students reported having been sexually harassed by both males and females. In addition, Mutekwe et al (2012) reported in their study that the majority of the girl participants indicated that it was boys and male teachers who harassed and sexually abused them at school.…”
Section: Literature Reviewmentioning
confidence: 99%
“…6 Beyond individual-level risk and protective factors, other research highlights or implies environmental (school-level) correlates of sexual victimization. For instance, research shows that there are particular areas of schools that experience a disproportionate share of overall sexual harassment, with "hot spots" including school hallways, classrooms, the gym, playing fields, or a pool area (AAUW, 2001;Walsh et al, 2007). A number of these spots overlap with the hot spots identified by Astor and colleagues (described above) in their study of general school violence (e.g., Astor et al, 1999;Benbenishty & Astor, 2005).…”
Section: Is It Opportunistic?mentioning
confidence: 89%
“…Both of the AAUW (1993AAUW ( , 2001) studies revealed that the majority of sexual victimization was committed by students. In addition, compared to male students, females were more likely to report that the perpetrator was a fellow student rather than an employee of the school (Walsh et al, 2007).…”
Section: Sexual Victimization At Schoolmentioning
confidence: 98%
“…Most students also experience some forms of sexual harassment during high school, either occasionally (59%) or often (27%), with girls experiencing more frequent and severe forms than boys [5,6]. Even when the timeframe of questions about unwanted sexual behaviors and harassment is narrowed from ''ever'' (i.e., lifetime prevalence) to the past 2 weeks, 15% of high school students report being subjected to unwanted and personally upsetting sexual harassment [7].…”
mentioning
confidence: 98%